Surgical scar management - an evaluation of surgical techniques - Căiță, Georgiana Albina; Lascu, Camelia Florentina; Bodog, Florian Dorel; Buhaș, Camelia Liana; Voiță-Mekeres, Florica; Voiță, Gheorghe Florin (Medicine and Pharmacy Reports, 2024)
The purpose of this narrative review is to analyze surgical techniques for removing scar tissue and minimizing them. A considerable proportion of the population have scars that are related to a traumatic event that they remember accurately, this being especially true for scars on the face, but also on the rest of the body if they are of significant size. The negative consequences of the esthetic damage are felt mainly in the family and at professional level, without losing sight of the fact that any person suffers as a result of the awareness of unsightly wounds or scars. To be successful, an aesthetic intervention must represent the optimal balance between science, the art of plastic surgery and the patient’s expectations. Good communication between surgeon and patient is also needed. We must state that there is no method of total removal of scars; even in the case of complex surgical techniques, the scar cannot be completely excised, but a much more aesthetic appearance can be obtained. Scars cannot be completely removed from the skin, they can improve their appearance by fading or thinning, initially by conservative treatment, later, if necessary, by surgical scar reduction techniques. Improving the appearance of a scar depends on the type of scar, its severity, its surface and location, the causing factors, the time elapsed from production to the application of specialized treatment.